تعليمية مقرر علم الصرف في الجامعة الجزائرية -سنة أولى آداب أنموذجا - دراسة تحليلية نقدية - سلمي, بن صغير, سهام آية (University of El-oued, 2022)
هذه الدراسة المعنونة ب "تعليمية مقرر علم الصرف في الجامعة الجزائرية –سنة أولى ليسانس آداب أنموذجا-دراسة تحليلية نقدية" تهدف إلى محاولة الكشف عن تعليمية مقرر علم الصرف في الجامعة الجزائرية، وتسليط الضوء على طرائق تعليم هذا المقرر ـ علم الصرف- وسبل تبسيط صعوباته لدى طلبة أولى ليسانس آداب. ومضمون هذه الدراسة كالآتي: تضم هذه الدراسة فصلين، الفصل الأول هو عبارة عن فصل نظري يحتوي على مصطلحات ومفاهيم هذه الدراسة، أما الفصل الثاني فهو عبارة عن فصل تطبيقي، وهو دراسة ميدانية حول تعليمية مقرر علم الصرف. This study entitled" educational course of exchange science at the University of Algeria –first year of The Bachelor of arts as a model-a critical analytical study " aims to try to reveal the educational course of exchange science at the University of Algeria, and to highlight the methods of teaching this course - Exchange science-and ways to simplify its difficulties for students of the first Bachelor of Arts. The content of this study is as follows: This study includes two chapters, the first chapter is a theoretical chapter containing the terms and concepts of this study, and the second chapter is an applied chapter, which is a field study on Educational Course exchange science.
Keywords: التعليمية، التدريس، المقرر، الصرف.; educational, teaching, course, Exchange